Kontribusi Hukum Pidana Islam terhadap Pembentukan Warga Negara yang Berkeadaban - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Aginra Falah Istiqomah; Muhammad Hazib Khoironi; Syahru Fajar Ibrahim (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Islamic criminal law significantly contributes to shaping a civilized citizenry through the enforcement of principles of justice, responsibility, and respect for human rights. This article aims to analyze how Islamic criminal law, with a maqasid al-shariah approach, provides a moral and ethical foundation for developing individual character as part of a civic community. The study identifies the core elements of Islamic criminal law, such as the concepts of hudud, qisas, and ta'zir, and examines their implementation in the context of a modern pluralistic state. Using a normative-juridical method and a comparative approach, this article explores the harmonization of Islamic criminal law with the positive legal system in Indonesia. The findings indicate that Islamic criminal law not only seeks to uphold legal justice but also aims to build a society rooted in ethical and civilized values. Integrating these values into national legal policies has the potential to strengthen a civic identity that is religious, just, and civilized, while respecting societal diversity. This article recommends enhancing Islamic legal education as a strategic effort to create synergy between Islamic criminal law and the development of exemplary citizens.